Fear of Missing Out (FoMO) and Self-Control in Relation to Compulsive Buying - Catur Prasetianingsih; Suroso; Pratitis, Niken Titi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study aims to analyze the relationship between Fear of Missing Out (FoMO) and self-control on compulsive buying via paylater services among teachers and employees of an Islamic elementary school in Surabaya. The sample consisted of 210 respondents, who were teachers and employees of an Islamic elementary school in Surabaya, aged between 20 and 40 years, residing in Surabaya, and actively using e-commerce platforms at least once a month. The data analysis technique used in this study was multiple linear regression. The results showed a significant relationship between Fear of Missing Out (FoMO) and self-control with compulsive buying via paylater services among teachers and employees of an Islamic elementary school in Surabaya (F = 613.145; p < 0.05), with a contribution of 85.6%. There was a positive relationship between Fear of Missing Out (FoMO) and compulsive buying via paylater services among teachers and employees of an Islamic elementary school in Surabaya (t = 7.789; p < 0.05), with a contribution of 49.3%. Additionally, there was a negative relationship between self-control and compulsive buying via paylater services among teachers and employees of an Islamic elementary school in Surabaya (t = -22.667; p < 0.05), with a contribution of 81.4%.